Synthetic oxepanoprolinamide iboxamycin is active against Listeria monocytogenes despite the intrinsic resistance mediated by VgaL/Lmo0919 ABCF ATPase. Issue 3 (17th June 2022) - Brodiazhenko, Tetiana; Turnbull, Kathryn Jane; Wu, Kelvin J Y; Takada, Hiraku; Tresco, Ben I C; Tenson, Tanel; Myers, Andrew G; Hauryliuk, Vasili
Abstract: Background: Listeriosis is a food-borne disease caused by the Gram-positive Bacillota (Firmicute) bacterium Listeria monocytogenes . Clinical L. monocytogenes isolates are often resistant to clinically used lincosamide clindamycin, thus excluding clindamycin as a viable treatment option. Objectives: We have established newly developed lincosamide iboxamycin as a potential novel antilisterial agent. Methods: We determined MICs of the lincosamides lincomycin, clindamycin and iboxamycin for L. monocytogenes, Enterococcus faecalis and Bacillus subtilis strains expressing synergetic antibiotic resistance determinants: ABCF ATPases that directly displace antibiotics from the ribosome and Cfr, a 23S rRNA methyltransferase that compromises antibiotic binding. For L. monocytogenes strains, either expressing VgaL/Lmo0919 or lacking the resistance factor, we performed time-kill kinetics and post-antibiotic effect assays. Results: We show that the synthetic lincosamide iboxamycin is highly active against L. monocytogenes and can overcome the intrinsic lincosamide resistance mediated by VgaL/Lmo0919 ABCF ATPase. While iboxamycin is not bactericidal against L. monocytogenes, it displays a pronounced post-antibiotic effect, which is a valuable pharmacokinetic feature. We demonstrate that VmlR ABCF of B. subtilis grants significant (33-fold increase in MIC) protection from iboxamycin, while LsaA ABCF of E. faecalis grants an 8-fold protective effect. Furthermore, the VmlR-mediated iboxamycin resistance is cooperative with that mediated by the Cfr, resulting in up to a 512-fold increase in MIC. Conclusions: While iboxamycin is a promising new antilisterial agent, our findings suggest that emergence and spread of ABCF ARE variants capable of defeating next-generation lincosamides in the clinic is possible and should be closely monitored.